PENGETAHUAN DAN SIKAP GURU AGAMA DAN GURU BP TERKAIT PENCEGAHAN PERKAWINAN ANAK UNTUK MENEKAN ANGKA STUNTING DI SMA WILAYAH KEK MANDALIKA - Zaim Syamsuddin (Jurnal Medika Hutama, 2024)
Child marriage is a serious problem faced by developing countries including Indonesia. Child marriage can cause disorders in obstetrics, perinatal period, Low Birth Weight (LBW), increased risk of prematurity, somatic health disorders, mental health disorders, and disorders in female reproduction, and can even result in stunting. The increasing number of child marriages can be caused by several factors, namely the family's economic level, place of residence/environment, knowledge about marriage, and level of education. The purpose of this study was to determine the knowledge and attitudes of Religious Teachers and Guidance Teachers regarding the Prevention of Child Marriage to Reduce Stunting Rates in Senior High Schools in the Mandalika Special Economic Zone. The respondents of this study consisted of 6 religious studies teachers and 8 guidance teachers (BP) who were spread across three schools, SMAN 1 Pujut, SMKN 1 Pujut, and SMAN 2 Pujut. The sampling method used was total sampling and used the snowball method to determine the keyperson. The assessment instruments used were questionnaires and interviews by preparing interview guidelines. Quantitative data analysis used descriptive and qualitative data used phenomenology. The results of the study show that the respondents' knowledge and attitudes are classified as good, but there are many things that can be related to each other in terms of knowledge and attitudes in daily activities in the school environment.